A robust and all-inclusive pipeline for shuffling of adeno-associated viruses - Herrmann, Anne-Kathrin; Kienle, Eike; Große, Stefanie; El Andari, Jihad; Botta, Julia; Schürmann, Nina; Wiedtke, Ellen; Niopek, Dominik; Grimm, Dirk (ACS synthetic biology, 2019)
Adeno-associated viruses (AAV) are attractive templates for engineering of synthetic gene delivery vectors. A particularly powerful technology for breeding of novel vectors with improved properties is DNA family shuffling, i.e., generation of chimeric capsids by homology-driven DNA recombination. Here, to make AAV DNA shuffling available to a wider community, we present a robust experimental and bioinformatical pipeline comprising: (i) standardized and partially codon-optimized plasmids carrying 12 different AAV capsid genes; (ii) a scalable protocol including troubleshooting guide for viral library production; and (iii) the freely available software SALANTO for comprehensive analysis of chimeric AAV DNA and protein sequences. Moreover, we describe a set of 12 premade and ready-to-use AAV libraries. Finally, we demonstrate the usefulness of DNA barcoding technology to trace AAV capsid libraries within a complex mixture. Our protocols and resources facilitate the implementation and tailoring of AAV evolution technology in any laboratory interested in customized viral gene transfer.